Pemberdayaan Mahasiswa Program Pembinaan Mahasiswa Wirausaha (P2MW) melalui pembuatan Lilin Aroma Terapi Berbahan Dasar Minyak Jelantah - Indah Wahyu Prastyo; Siska Adelia Putri; Dewanti Nastiti; Awin Mulyati (Politeknik Kampar, 2024)
This research explores the potential of utilizing used cooking oil and other aromatherapy ingredients as candle materials. By utilizing used cooking oil as the main raw material, the business not only supports sustainability by recycling waste, but also produces environmentally friendly products. These aroma therapy candles are designed to provide a relaxing and health- beneficial experience through the combination of essential oils. The meticulous production process ensures that each candle is of the highest quality, making it a top choice for consumers who are environmentally conscious and looking for unique aroma therapy solutions. In addition to the sustainability aspect, the business also highlights wellness values by using essential oils that can provide psychological and physical benefits. Product uniqueness, attention to detail, and environmental awareness make the used cooking oil aroma therapy candle business an attractive option in a competitive market.